A new hybrid method for solving variational inequalities - Malitsky, Yu.V.; Semenov, V.V. (Доповіді НАН України, 2014)
We introduce a new method for solving variational inequalities with monotone and Lipschitzcontinuous operators acting in a Hilbert space. The iterative process based on the well-known
projection method and the hybrid (or outer approximations) method. However, we do not use
an extrapolation step in the projection method. The absence of one projection in our method
is explained by a slightly different choice of sets in the hybrid method. We prove the strong
convergence of the sequences generated by our method. Запропоновано новий гiбридний метод для розв’язання варiацiйних нерiвностей з монотонними i лiпшицевими операторами, що дiють у гiльбертовому просторi. Iтерацiйний процес базується на двох добре вiдомих методах: проективному та гiбридному (або зовнiшнiх
апроксимацiй). Причому не використовується екстраполяцiйний крок у проективному методi. Вiдсутнiсть однiєї проекцiї досягається шляхом iншого вибору наборiв множин у гiбридному методi. Доведено сильну збiжнiсть породжених методом послiдовностей. Предложен новый гибридный метод для решения вариационных неравенств с монотонными
и липшицевыми операторами, действующими в гильбертовом пространстве. Итерационный процесс основан на двух хорошо известных методах: проективном и гибридном (или
внешних аппроксимаций). Причем не используется экстраполяционный шаг в проективном
методе. Отсутствие одной проекции достигается путем иного выбора наборов множеств
в гибридном методе. Доказана сильная сходимость порожденных методом последовательностей.